La Migración como Proceso El Concepto de Temporalidad en Blogs de Migrantes Latinoamericanos a Quebec - Frank-Job, Barbara (Ensayos InterAmericanos, 2020)
The blogs of immigrants to Quebec document migration as a narrative (re)construction of the processes of experiences that are negotiated in the blogging community of the immigrants. In the course of this protracted process of negotiation and signification, different concepts of temporality play an essential role. They originate in two fundamentally different areas of discourse: first, they are rooted in the institutional discourse of Canadian immigration policy (which defines immigration as a parcours) and second, they emerge in immigrants' personal experiences and emotions, which are linked to their own immigration project. Using the example of an extensive corpus of web blogs of Latin American immigrants to Quebec and within the methodological framework of discourse analysis and conversational linguistics, my essay examines the forms, functions, and meanings of the construction of the concepts of temporality of migration.